Association of condylar position with anterior disk displacement and disk morphology in patients with internal derangement of the TMJ: a study with axially corrected sagittal tomography and MRI - OZAWA, So; TAGUCHI, Akira; TANIMOTO, Keiji; SUEI, Yoshikazu; SUGIYAMA, Hiroki; TANNE, Kazuo (Journal of the Japanese Society for the Temporomandibular Joint, 1997)
This study was conducted to elucidate the association between condylar position, and disk displacement and disk morphology for patients with internal derangement of the TMJ. Thirty-two patients with internal derangement of the TMJ were used as subjects and the 50 joints without any deformation of the condyle were studied. All the joints were deviled into ADDW (anterior disk displacement with reduction) group, ADDWO (anterior disk displacement without reduction) group and N (no disk displacement) group according to the MRI findings on the nature of disk displacement. The anterior and posterior joint spaces were measured on the axially corrected sagittal tomograms. A-P ratio (anterior joint space/posterior joint space) was significantly larger in the ADDW group than in the N group, whereas the value was not statistically different from those in the ADDWO and N groups. It is shown that condylar position is highly associated with the nature of disk displacement for patients with internal derangement of the TMJ.